2008
DOI: 10.1007/s11390-008-9187-y
|View full text |Cite
|
Sign up to set email alerts
|

A Semantic Cache Framework for Secure XML Queries

Abstract: Secure XML query answering to protect data privacy and semantic cache to speed up XML query answering are two hot spots in current research areas of XML database systems. While both issues are explored respectively in depth, they have not been studied together, that is, the problem of semantic cache for secure XML query answering has not been addressed yet. In this paper, we present an interesting joint of these two aspects and propose an efficient framework of semantic cache for secure XML query answering, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Several alternative semantic cache architectures for semi-structured data were presented in Feng, Li, and Ta (2008), Hristidis (2002), Li and Feng (2010), Sumalatha et al (2007), Xu (2005), Zhan et al (2006). The problem of partial query matching was studied in Sumalatha et al (2007).…”
Section: Related Workmentioning
confidence: 99%
“…Several alternative semantic cache architectures for semi-structured data were presented in Feng, Li, and Ta (2008), Hristidis (2002), Li and Feng (2010), Sumalatha et al (2007), Xu (2005), Zhan et al (2006). The problem of partial query matching was studied in Sumalatha et al (2007).…”
Section: Related Workmentioning
confidence: 99%
“…Considering Q 1 , as SubQueryMatch(Infix(V, 1), 3)) is true, QR 2 1 = VR 2 1 and QR 3 1 = VR 3 1 . We get FVR MP in line 8 by processing the main path of view V as illustrated in Fig.6.…”
Section: Ample Suppose P = A[c[d]/e]/b[e[f ]/G] and Q = A[c[d][e]]/bmentioning
confidence: 99%
“…In a relational database system, the in-memory buffer cache is crucial for good performance, and a similar buffer cache can be employed in XML systems. Maintaining semantic cache of query results has been proposed [1][2][3] . They address the computational cost and complement the buffer cache.…”
Section: Introductionmentioning
confidence: 99%
“…While some research has defined the concept of environmental management accounting and has reported current practices [2], other studies have examined the role of accounting in environmental management [3,4] and issues related to environmental cost accounting [5,6]. Some believe the environmental performance evaluation have many benefits [7].…”
Section: Introductionmentioning
confidence: 99%